Análisis de la gestión gerencial en la compañía de transporte pesado Comboy Sur de la ciudad de Quito - Negrete Caiza, Fanny Susana (2023)
Managerial Management consists by assuming responsibilities on carrying out a business or personal process, by coordinating tasks in order to solve, organize, direct and control activities for the proposed aims fulfillment. The investigative work is focused on analyzing the Manager Management handle, getting current management true data made by the Heavy Transport Comboy Sur company, for this purpose, it will be applied a quantitative research, what allows to base the numerical data process and analysis on the variable called Management Manager with a non experimental design based on cross-sectional or transactional studies, these are developed about the 30 employees from company, collecting data only once from each study subject, the methodologies used are bibliographic, descriptive and deductive, since it is the means, which allowed systematizing and ordering the got information. The used technique is the survey, through the study instrument, which will be the questionnaire properly said, what is made up 24 questions related to planning, organization, direction and control focused on communication, motivation, leadership, training and philosophy, using strategies and technologic tools, which allows analyzing research specific measures from company's problem, for improving the workplace, in order to generate responsibility and commitment each employee. Seen in this way, the research has to propose technological tools with strategic guidelines, what help to make with the handle proper of the manager management, directly benefiting the organization, maintaining competitive advantages in relation to competitors.